The association of body mass index (bmi) with clinical outcomes in patients with pulmonary tuberculosis - Muhamad, Dzawani (2011)
INTRODUCTION Tuberculosis is becoming an increasingly important problem worldwide especially with the alarming increase in the incidence of acquired immunodeficiency syndrome (AIDS). The association of Body Mass Index (BMI) with clinical outcomes of patients with pulmonary tuberculosis had been studying worldwide but local data is lacking. Previous studies showed that BMI can be used as a screening tools for the nutritional status. Low BMI has a strong relationship with risk of tuberculosis and high BMI has been shown to be protective against tuberculosis (TB) among HIV negative individuals, as well as against disease progression and mortality among those with HIV. This study is designed to evaluate the association of BMI with clinical outcomes in patients with pulmonary tuberculosis. METHODS This study was conducted in new patients registered with pulmonary tuberculosis (PTB) in a Respiratory Clinic, Hospital Universiti Sains Malaysia from May 2010 to may 2011. The objective of this study was to study the association between body mass index (BMI) and clinical outcomes in patients with PTB (defined as sputum conversion rate, weight gain and adverse drug reactions). xi RESULTS There were 127 patients (68 men and 59 women) were recruited in this study whose 123 TB patients (96.1%) were new PTB and 4 PTB patients (3.1%) were relapse PTB. 81 patients (63.3%) had PTB smear positive, 45 patients (35.2%) had PTB smear negative and 1 patients (0.8%) had miliary TB. 65 patients (49.3%) were underweight on admission ( body mass index (BMI) <18.5 kg/m² ). There were 50 patients (41.2%) were normal weight ( BMI 18.50-24.99 kg/m²), 10 patients (7.4%) were overweight (BMI ≥25 kg/m²) and 2 patients (2.0%) were obese (BMI ≥30 kg/m²). 102 patients (95.4%) had weight increment, 98 patients (77.0%) had sputum conversion and 12 patients (9.0%) had adverse drug reactions (ADRs). Univariate analysis showed no significant association between BMI group and clinical outcomes of PTB (p>0.05). CONCLUSION As a conclusion, majority of the patients who were diagnosed to have pulmonary TB were underweight. Majority of the patients had a good smear positive response (64-100%) and weight gain (74-100%), irrespective of BMI groups. 12% of the patients developed allergic drug reactions and mostly from lower BMI groups.